Attitudes of Educated Nigerians towards Varieties of English. Issue 1 (2nd January 2022) - Olatoye, Temitayo
Abstract: This study examines the attitudes of 102 Nigerians towards six varieties of English in terms of status and solidarity: Southern British, Scottish, General American, Acrolectal Nigerian, Non-acrolectal Nigerian, and Ivorian. Using the verbal guise technique, attitudinal evaluations were obtained via an online questionnaire with a six-point semantic differential scale and eight traits. A speaker identification task was also included to examine dialectal awareness. Results indicate that the British, American, and Acrolectal Nigerian varieties received more positive evaluations in terms of status, while greater solidarity was expressed towards the American and both Nigerian varieties. An examination of participants' responses reveals that accent familiarity and the speaker's degree of accentedness enhance the listener's ability to make fine-grained distinctions. These findings are discussed in relation to the acceptability of an endonormative variety in Nigeria.